The Ottoman Response to the Portuguese-Acehnese Conflicts in the 16th Century - Hakim, Lukman; Murodi, Murodi; Rahman, Andi (UIN Sunan Gunung Djati Bandung, 2024)
This research investigates the diplomatic correspondence between the Acehnese Sultanate and the Ottoman Empire during the 16th century, shedding light on the transregional alliances that shaped geopolitical dynamics in Southeast Asia. The study employs a structured historical methodology, encompassing heuristics (data collection), verification (authentication of sources and authors), interpretation (critical analysis), and historiography (historical synthesis). The findings reveal a series of preserved letters in the Ottoman archives, documenting official communications during the reign of Sultan Alauddin al-Kahar of Aceh, notably, correspondence with Ottoman rulers Sultan Suleiman the Magnificent and Sultan Selim II highlights Aceh’s strategic efforts to secure Ottoman support against Portuguese expansion in the Indian Ocean. Sultan Alauddin al-Kahar’s letters detail three primary requests: formally recognizing Aceh as an Ottoman vassal state, military assistance including cannon makers, naval vessels, and fortification materials, and the dispatch of military advisors and trainers. The records further confirm that the Ottoman Empire responded positively, demonstrating a willingness to assist Aceh, reflecting shared interests in countering Portuguese influence. This study contributes to a nuanced understanding of early modern diplomacy and the interconnected nature of political and military networks across the Indian Ocean, emphasizing the Ottoman Empire’s pivotal role in supporting regional powers like Aceh. Keywords: response, Acehnese, Ottoman, sultan.